Analisis Kelayakan Aspek Ekonomi dan Kapasitas Biodigester Model Fix Dome Plant (Studi Kasus Biodigester di Botokenceng, Yogyakarta) - Monica, Fanny (Semesta Teknika, 2013)
Beside faeces and urine from cattleâs digestion, ruminants produce highly enough methane gas (CH4). This Methane Gas is one of the gases that influence the global warming and ozone decay, with rate 1% per year and still increasing. Biogas reactor is one of the solutions to solve those problems. This research aims to find out the capacity and economic feasibility of biodigester model Fix Dome Plant located in Botokenceng, Banguntapan, Yogyakarta. Primary data which are measurements and documentation, as well as the sketch (AutoCAD) and budget plan as secondary data, were analysed in this study. The formulas to obtain the capacity of biodigester are the equation of cowâs faeces volume and faeces solvent volume. Meanwhile, Benefit Cost Ratio (B/C) and Break Even Point (BEP) were used for economic analysis. The results of this study show that the average debit was 140.7 litres/day, with average speed for different height of flume was 4.0225 m/day. Furthermore, the operational debit was 84.4 litres/minute, with average speed for varying height of flume was 2.36 m/minute. Biodigester capacity based on digester size was 4.22 m3 which can contain faeces from 2.67 cows so that the volume needed for the biodigester was 6.33 m3 since there are four cows. According to the budget plan, the investment to build the biodigester was Rp 12,821,354.50.-. The budget earned from 4 cows was Rp 6,532,165.-/year, while the expenses were Rp 1,466,160.-/year. The result of B/C analysis was 4.45 (B/C > 1), and BEP analysis occurred at the 7th year with total income was Rp 37,925,750.-.